Coordination Failure with Multiple-Source Lending: The Cost of Protection against a Powerful Lender - Franz Hubert; Dorothea Schäfer (Journal of Institutional and Theoretical Economics, 2002)
We analyze how a firm might protect quasirents in an environment of imperfect capital markets, where switching lenders is costly to the borrower, and contracts are incomplete. As switching costs make the firm vulnerable to ex post exploitation, it may want to diversify lending. Multiple-source lending, however, suffers from coordination failure. An uncoordinated withdrawal of funds will force a financially distressed firm into bankruptcy even though it could have been rescued if lenders had stayed firm. We show that the gains from preventing renegotiation do outweigh the cost of coordination failure if a single lender has sufficient bargaining power.
Additional information: The final publication is available from Mohr Verlag via http://dx.doi.org/10.1628/0932456022975394
Keywords: 330; Wettbewerbstheorie; Insolvenz; Theorie